2002
DOI: 10.1590/s0100-06832002000300008
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de nitrogênio e produtividade da cana-de-açúcar (cana-planta) em solo arenoso com incorporação de resíduos da cultura

Abstract: RESUMOCom o objetivo de avaliar a produção da cana-de-açúcar (cana-planta) e a utilização do N da uréia aplicada no plantio, com incorporação de restos culturais ao solo (raízes, rizomas, colmos, ponteiro e folhas secas), desenvolveu-se um experimento em vasos (220 L) que continham terra de textura arenosa. Os fatores de estudo foram: doses de N no plantio 0, 30, 60 e 90 kg ha -1 de N-uréia marcada com 15 N e restos culturais de cana-de-açúcar incorporados ao solo, com ou sem folhas secas. O delineamento exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
74

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(102 citation statements)
references
References 13 publications
2
25
1
74
Order By: Relevance
“…This author concluded that, in the case of negative responses to N in the sugar content on sugarcane stalks, the N levels that maximize this factor are lower than those that provide the highest TCH. Therefore, the sugar yields (TSH) observed in the present work were linearly different among N treatments in plant cane and ratoons, due to the variation in cane yield per hectare (TCH) (Figures 2 and 3), which is in accordance with findings of Orlando Filho et al (1994), Korndörfer et al (1997Korndörfer et al ( , 2002, and Trivelin et al (2002).…”
Section: Resultssupporting
confidence: 92%
“…This author concluded that, in the case of negative responses to N in the sugar content on sugarcane stalks, the N levels that maximize this factor are lower than those that provide the highest TCH. Therefore, the sugar yields (TSH) observed in the present work were linearly different among N treatments in plant cane and ratoons, due to the variation in cane yield per hectare (TCH) (Figures 2 and 3), which is in accordance with findings of Orlando Filho et al (1994), Korndörfer et al (1997Korndörfer et al ( , 2002, and Trivelin et al (2002).…”
Section: Resultssupporting
confidence: 92%
“…These authors reported that 7 % of the N applied to sugarcane shoots was translocated to the root system and later used during sugarcane regrowth. Possibly, this nutrient translocation is a mechanism ensuring greater vigor of the root system and regrowth of a next cycle (Trivelin et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the difficulties of N fertilizer management on green cane, studies rarely report the use of more than 40 % of fertilizer N by sugarcane (Trivelin et al, 2002). This low recovery is partly attributed to the residual effect in the soil due to the high N fertilizer immobilization, and to N losses in the soilplant-atmosphere system.…”
Section: Introductionmentioning
confidence: 99%
“…O sistema radicular da cana-de-açúcar (rizomas e raízes) é essencial para a rebrota das soqueiras, uma vez que cumpre o papel de reserva orgânica energética e nutricional (Camargo, 1989;Malavolta, 1994;Trivelin et al, 2002). Ao mesmo tempo em que ocorre a brotação das socas, um novo sistema radicular é formado, e algumas raízes vivas são importantes para alimentar os rebentos na fase inicial de desenvolvimento (Casagrande, 1991).…”
Section: Introductionunclassified